2012
DOI: 10.1179/1743284711y.0000000014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alloying on mechanical properties of as cast ferritic nodular cast irons

Abstract: . Effect of alloying on mechanical properties of as cast ferritic nodular cast irons. Materials Science and Technology, Maney Publishing, 2012, vol. 28, pp. 184-191. 10 The development of low temperature applications for ferritic nodular cast irons calls for improved materials in the as cast state, e.g. for off-shore windmills components. Within this line of work, a series of 68 castings were prepared with the same casting procedure and slight changes in composition. The tensile properties at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Such a variability has been observed by Sertucha et al 41) who reported that the nodule count (N A ) varied from 190 mm − 2 to 590 mm − 2 at given casting and inoculation conditions. The composition ranges of the four series of alloys that were investigated are given in Table 2 for the main elements and Table 3 for the low level elements.…”
Section: Impurities and Trace Elements Effectsmentioning
confidence: 80%
“…Such a variability has been observed by Sertucha et al 41) who reported that the nodule count (N A ) varied from 190 mm − 2 to 590 mm − 2 at given casting and inoculation conditions. The composition ranges of the four series of alloys that were investigated are given in Table 2 for the main elements and Table 3 for the low level elements.…”
Section: Impurities and Trace Elements Effectsmentioning
confidence: 80%
“…In all cases, higher silicon contents reduce the measured impact energy for rupture as this element strongly increases the ductile to brittle temperature. 2,16 A maximisation of UTS and Y parameters leads to select the highest silicon contents while keeping the maximum value of elongation. Thus, a high silicon range (3?75-3?80 wt-%) combined with an intermediate range for carbon (3?30-3?40 wt-%) seems to be adequate as it has been stated previously in relation with Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained cast parts were standard keel blocks. 2 Inoculation treatment was carried out by adding 0?014 kg (0?20 wt-%) of a commercial inoculant (grain size 0?2-0?5 mm, Si569?9 wt-%, Al50?93 wt-%, Ca5 1?38 wt-%, Bi50?49 wt-% and rare earth50?37 wt-%) into the cavity of the moulds before pouring them. Chemical compositions for all significant elements are shown in Table 1, which does not include the contribution of inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…All details on melt preparation and casting procedures have already been given Sertucha et al, 2012;De la Torre et al, 2014). In the present work, only results obtained on materials cast in standard keel-blocks (type II according to EN 1563) and in as-cast state will be considered.…”
Section: Experimental Informationmentioning
confidence: 99%